Specifying Bolt Length for High-Strength Bolts - Carter, Charles J. (Engineering Journal, 1996)
Two tables that are useful in determining the proper bolt length for high-strength bolts are provided in the AISC Manual of Steel Construction: Table 8-2, which includes constants to be added to the grip and washer thickness (RCSC Specification Table C2 is the basis for these constants) and a table in Figure 8-3, which indicates the outer-ply thickness required to exclude the threads from the faying surface of the connection. While it is a simple operation to select bolt lengths using these tables, the repetitive calculation becomes somewhat tedious and could be simplified. In this paper, a design aid is presented for the selection of high-strength bolt lengths for bearing (snug-tightened and fully tensioned) and slip-critical connections. Nominal bolt lengths are tabulated based upon the grip in ASTM A325 and A490 bolts with zero, one, or two 5/32-in.-thick ASTM F436 flat washer(s) and an ASTM A563 nut; bevelled washers are not considered in this paper. Additionally, the outer-ply thickness required when it is desired to exclude the threads from the shear plane is tabulated.